Profitability and agronomic potential of cotton (Gossypium hirsutum L.) under biochar-compost-based amendments in three agroecological zones of northern Benin - Tovihoudji, G. Pierre; Diogo, Rodrigue V. Cao; Abiola, Waliou A.; Akoha, Fred B. R. M.; Godau, Tobias (Frontiers in Sustainable Food Systems, 2022)
Low land productivity is a major constraint facing agriculture in sub-Saharan Africa, which severely affects crop yields, particularly cotton which is main export agricultural produce of Northern Benin. To overcome this situation, the hill-placement of microdose biochar-compost-based amendments was carried out at two research stations and on farmer's fields in three agroecological zones of northern Benin. The study aims to evaluate the agronomic and economic performance of cotton under two types of compost and biochar-based amendments. On stations, the experimental design used was a complete randomized block with one factor and ten treatments replicated four times as follows: (i) absolute control without any amendment (Ck), (ii) mineral fertilizer (MF) at 200 kg/ha, (iii) cow dung-based compost at 200kg/ha (CP1_200) and (iv) 300kg (CP1_300), (v) household waste-based compost at 200kg/ha (CP2_200) and (vi) 300 kg (CP2_300), the combination of CP1 and 15% biochar designated Terra preta (TP) applied at 200kg/ha (vii, TP1_200) and 300kg/ha (viii, TP1_300), the combination of CP2 and 15% biochar applied at 200kg/ha (ix, TP2_200) and 300kg/ha (x, TP2_300). On-farms, the experimental design was a randomized complete block with one factor and six optimal treatments extracted from the on-station experiments with three replicates installed in four farmers' fields from each location studied. The six treatments were: Ck, MF, CP1_200, CP2_200, TP1_200 and TP2_200. Cotton growth (Plant height, number of vegetative and reproductive branches and total bolls per plant) and yield data were collected. The treatment TP1_300 yielded higher cotton seed with 2.53 t/ha, i.e., 86% more than the absolute control. However, the highest plant growth parameters were obtained with MF which were similar to those obtained with TP1_300 (P > 0.05). Likewise, at farms, the highest plant growth parameters and yield were observed with MF followed by TP1_200 (with a cotton seed yield increase of 146% compared to the control, P < 0.05). In addition, no significant differences were observed between organic fertilizers treatments for growth variables. However yield differences occurred. To resume, TP1_300 kg/ha performed best in terms of growth and yield in on-station experiments, while on-farms, TP1_200 kg/ha produced the highest responses of cotton. Value Cost Ratio (VCR) and Benefit Cost Ratio (BCR) values were generally as good or even better for MF treatment and treatments involving CP1 at both on station and on farm, compared to Ck. Although applying mineral fertilizer (MF) alone as currently done by many farmers appears to make economic sense, this practice is unlikely to be sustainable in the long term. Applying TP1_200 and TP1_300 are two possible strategies that are affordable to farmers and provide returns on investment at least as good as the current practice of sole application of MF. However, a long-term study to assess the effect of compost-activated biochar on crop productivity and soil quality is advised.